192k views
4 votes
Enter your answer and show all the steps that you use to solve this problem in the space provided.

f(x)+9x^3+2x^2-5x+4 and g(x)=5x^3-7x+4

What is f(x)-g(x)?

Show all of your steps and write your final answer in factored form.


I would like it if you put down all the steps and explanation for I do not understand it. Thank you so much for your help in advance!

User SteelBytes
by
5.7k points

1 Answer

2 votes

Answer:


\boxed{f(x) - g(x) = 2x(2x^(2) + x + 1)}

Explanation:

f(x) = 9x³ + 2x² - 5x + 4; g(x)=5x³ -7x + 4

Step 1. Calculate the difference between the functions

(a) Write the two functions, one above the other, in decreasing order of exponents.

ƒ(x) = 9x³ + 2x² - 5x + 4

g(x) = 5x³ - 7x + 4

(b) Create a subtraction problem using the two functions

ƒ(x) = 9x³ + 2x² - 5x + 4

-g(x) = -(5x³ - 7x + 4)

ƒ(x) -g(x)=

(c). Subtract terms with the same exponent of x

ƒ(x) = 9x³ + 2x² - 5x + 4

-g(x) = -(5x³ - 7x + 4)

ƒ(x) -g(x) = 4x³ + 2x² + 2x

Step 2. Factor the expression

y = 4x³ + 2x² + 2x

Factor 2x from each term

y = 2x(2x² + x + 1)


\boxed{f(x) - g(x) = 2x(2x^(2) + x + 1)}

User Gowri
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.